Вивчення клітинної локалізації протеїнкінази KIN10 з Arabidopsis thaliana - Краснопьорова, О.Є.; Ісаенков, С.В.; Ємець, А.І.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2015)
Aims. Protein kinase KIN10 from Arabidopsis thaliana, is one of the key regulator of response formation to different types of abiotic stress. To get insight of the molecular mechanisms of cellular response regulation to the various factors the study of KIN10 is very important. In order to evaluate the KIN10 cellular localization to continue experiments with colocalization the plasmid construct pGWR7-KIN10-BFP was created. Methods. The coding sequence of KIN10 was cloned using various molecular methods including PCR, RT-PCR. In order to check functionality of created construct the isolation and transformation of protoplasts were performed. Results. The plasmid construct pGWR7-KIN10-BFP with coding sequence of KIN10 was created. The intracellular localization of KIN10 was evaluated by transient expression in plant cells. It was found that KIN10 is uniformly distributed throughout the cell cytoplasm. Conclusions. We have created vector construct pGWR7-KIN10-BFP. It has been shown the ability of this construct to express within the cell and produces chimerical KIN10-BFP fusion protein. This construct can be useful for further colocalization study with cytoskeleton elements in order to evaluate the role of this kinase in the regulation of cytoskeleton. Our study demonstrates cytoplasmic localization of KIN10 kinase.